Prevalence of migraine among post graduate medical students - Manandhar, Naresh; Paudel, Leela (Journal of Chitwan Medical College, 2026)
Introduction: Migraine is a common primary headache disorder. This study aimed to find the prevalence and triggers of migraine among postgraduate medical students in Nepal. Methods: A cross-sectional study was conducted from Jul to Dec 2024 among postgraduate medical students at the Nepalese Army Institute of Health Sciences, Kathmandu, Nepal. Ethical approval was obtained. Inclusion criteria: all clinical postgraduate students. Exclusion criteria: comorbidities. Migraine was assessed based on ICHD-3 criteria. Data were collected via a self-administered questionnaire and analyzed using IBM SPSS version 22. Descriptive statistics and Pearson chi-square test were used with p-value <0.05 considered significant. Results: Among the participants (n=90), the prevalence of migraine was 15(16.7%). It was higher in females 9(25.0%) than males 6(11.1%) [OR=2.379; 95% CI: 0.767–7.386; p=0.139]. The most common triggers were stress 14(93.3%), skipping meals/hunger 12(80.0%), prolonged computer work 7(46.7%), and menstruation among females 5(55.6%). Conclusions: Migraine is common among postgraduate medical students, with stress as the leading trigger. Interventions to manage stress and lifestyle factors may help reduce its burden.